Iowa Birdline update, September 26, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for September 26, 1994. Highlights of the update include observations of large concentrations of American White Pelicans at several locations as well as numerous reports of Red-breasted Nuthatches. Also of note are sightings of a Parasitic Jaeger, Yellow Rails, Sharp-tailed Sparrows, and an unconfirmed report of an Anhinga from Marion County. Also included are handwritten notes for the next week's update with sightings of 8 American Avocets and a Black-throated Blue Warbler. Epson - sheet feed/flatbed